Conformity of Capital Provisions for Foreign Investors in the Regulations of the Investment Coordinating Board of the Republic of Indonesia - Moch Andry Mamonto; Inas Syahria (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
Foreign investors tend to be disadvantaged by the existence of new regulations which are derivatives of the work copyright law, so a study will be carried out and compiled to analyze the Conformity of Capital Provisions for Foreign Investors in Regulation of the Investment Coordinating Board of the Republic of Indonesia No. 4 of 2021 with laws and regulations regarding investment. The results of the research show that Law Number 11 of 2020 concerning Job Creation and Law Number 25 of 2007 do not regulate capital in setting capital requirements for foreign investment. So that legal uncertainty arises because the minimum investment value is equated with the minimum paid-up capital, while the paid-up capital is only 25% of the capital which implies that PMA must have capital of Rp. 40,000,000,000,000.00 because the paid-up capital is at least Rp. in Presidential Regulation Number 10 of 2021, the investment value is also IDR 10,000,000,000,000.00. In UUPM, PMA must be in the form of a Limited Liability Company, so based on UUPT, the issued capital must be 25%, so the law should strictly regulate capital requirements in foreign investment to create legal certainty.